A Phase I, Double-blind, Randomized, Placebo-controlled, Single Dose-escalation Study to Evaluate the Tolerability, and Safety of Cytisinicline in Adult Smokers. Issue 4 (5th October 2022) - Jacobs, Cindy; Fonseca, Marlene; Rigotti, Nancy A; Benowitz, Neal; Clarke, Anthony; Cain, Dan
Abstract: Introduction: Cytisinicline is a nicotinic acetylcholine receptor partial agonist marketed historically as oral tablets in Central and Eastern Europe as an aid to smoking cessation. Dosing and scheduled regimen for cytisinicline treatment is currently being redeveloped for market approval in the United States and elsewhere. Aims and Methods: A phase 1, double-blind, randomized, placebo-controlled, single-ascending dose clinical trial was conducted under fasting conditions in healthy adults who were current daily ( > 10 cigarettes) smokers. Safety parameters for the identification of a maximum tolerated dose (MTD) and limited supportive pharmacokinetic assessments were evaluated. Ascending single oral doses of cytisinicline or placebo were administered to 9 cohorts, each comprised of eight unique participants (randomization: 6 cytisinicline; 2 placebo). Dose escalation to the next cohort was dependent upon the safety review of preceding cohorts. Dose levels tested were 6, 9, 12, 15, 18, 21, 24, 27, and 30 mg. Treatment-emergent adverse events (TEAEs) and clinically relevant changes in laboratory blood tests, vital signs, and 12-lead electrocardiograms were evaluated. Results: Seventy-two participants completed the study (54 cytisinicline; 18 placebo). Nausea was the most common TEAE (10 participants [19%]). The MTD was defined as cytisinicline 30 mg based on gastrointestinal symptoms, predominantly vomiting (2 of 6 subjects, 33%). Maximum plasma concentration (observed Cmax ) values appeared to plateau at higher dose levels (beyond 24 mg). Conclusions: Single cytisinicline doses up to 30 mg were well tolerated and raised no new safety concerns in fasting adult smokers. An increased frequency of gastrointestinal symptoms defined the MTD at 30 mg. Implications: The cytisinicline therapeutic dose being evaluated in phase 3 clinical trials is 3 mg, which is a 10-fold lower dose than the 30 mg MTD level for cytisinicline, resulting in an excellent safety margin.